Economic Plants of Tripura State X. Plants Yielding Dyes - Deb, D. B. (Indian Forester, 1981)
The present paper is a part of a series of papers on economic plants of Tripura State contributed to this journal. It gives an account of the dye yielding plants occurring in this State.